Endoplasmic Reticulum Stress-Mediated Hippocampal Neuron Apoptosis Involved in Diabetic Cognitive Impairment. (24th April 2013) - Zhang, Xiaoming; Xu, Linhao; He, Daqiang; Ling, Shucai
Abstract : Poor management of DM causes cognitive impairment while the mechanism is still unconfirmed. The aim of the present study was to investigate the activation of C/EBP Homology Protein (CHOP), the prominent mediator of the endoplasmic reticulum (ER) stress-induced apoptosis under hyperglycemia. We employed streptozotocin- (STZ-) induced diabetic rats to explore the ability of learning and memory by the Morris water maze test. The ultrastructure of hippocampus in diabetic rats and cultured neurons in high glucose medium were observed by transmission electron microscopy and scanning electron microscopy. TUNEL staining was also performed to assess apoptotic cells while the expression of CHOP was assayed by immunohistochemistry and Western blot assay in these hippocampal neurons. Six weeks after diabetes induction, the escape latency increased and the average frequency in finding the platform decreased in diabetic rats (P < 0.05 ). The morphology of neuron and synaptic structure was impaired; the number of TUNEL-positive cells and the expression of CHOP in hippocampus of diabetic rats and high glucose medium cultured neurons were markedly altered (P < 0.05 ). The present results suggested that the CHOP-dependent endoplasmic reticulum (ER) stress-mediated apoptosis may be involved in hyperglycemia-induced hippocampal synapses and neurons impairment and promote the diabetic cognitive impairment.